2022
DOI: 10.3390/ijgi11080457
|View full text |Cite
|
Sign up to set email alerts
|

Make It Simple: Effective Road Selection for Small-Scale Map Design Using Decision-Tree-Based Models

Abstract: The complexity of a road network must be reduced after a scale change, so that the legibility of the map can be maintained. However, deciding whether to show a particular road section on the map is a very complex process. This process, called selection, constitutes the first step in a sequence of further generalization operations and it is a prerequisite to effective road network generalization. So far, not many comprehensive solutions have been developed for effective road selection specifically at small scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…The supervised selection methods of road networks have become a focal point of current discussions. With the rapid evolution of artificial intelligence, various techniques, including kernel machine learning [22], BP (back propagation) neural networks [23], Radial Basis Function [24], decision-tree-based (DT) models [25], and ontology knowledge reasoning [26], have been progressively applied to automate road network selection. And it has been demonstrated that road networks selected using machine learning models are extremely similar to the atlas maps [27],Despite these advancements, most supervised selection methods overlook the topological information inherent in road networks.…”
Section: Introductionmentioning
confidence: 99%
“…The supervised selection methods of road networks have become a focal point of current discussions. With the rapid evolution of artificial intelligence, various techniques, including kernel machine learning [22], BP (back propagation) neural networks [23], Radial Basis Function [24], decision-tree-based (DT) models [25], and ontology knowledge reasoning [26], have been progressively applied to automate road network selection. And it has been demonstrated that road networks selected using machine learning models are extremely similar to the atlas maps [27],Despite these advancements, most supervised selection methods overlook the topological information inherent in road networks.…”
Section: Introductionmentioning
confidence: 99%